The Role of Spirituality in Fraud Prevention with the Government Internal Control System as a Mediator in Village Fund Management - Kusumastuti, Endah Dwi; Afriady, Arif (Management Science Research Journal, 2024)
Spirituality creates interconnectedness between beings and has the potential to transform the workplace into something extraordinary. SPIP and spirituality are complementary components. SPIP is an integral process in actions and activities carried out continuously by all employees until the organization's goals are achieved. Fraud prevention in village fund management is an urgency considering the contribution of expenditure to the Village Budget continues to increase, so that this study is needed to see the influence of both variables on fraud prevention. This study analyzes the Smart Pls-assisted path using a questionnaire in 9 villages in Kotabaru District, Karawang. The results of this study indicate that spirituality has an influence on fraud prevention and SPIP has an influence as a mediator. This study shows that village officials need to develop activities or motivation to increase spirituality which will have an impact on the government's internal control system and fraud prevention.